Study on peak expiratory flow rate and its influencing factors in healthy school children in Kancheepuram district of Tamil Nadu, India - D., Ramamani; Kannan, Iyanar (International Journal of Contemporary Pediatrics, 2020)
Background: The Peak Expiratory Flow Rate (PEFR) is useful to screen and monitor the severity of asthma in children. Many studies have documented that age, height and weight are some of the main factors that affect the PEFR. Thus, the present study was done to find the PEFR values among the school children and to find the factors that influences the PEFR values in our geographical area. Methods: It was a cross sectional study conducted in school children belong the rural area of Kancheepuram district, Tamil Nadu, India. A total of 378 students of both the gender at the age group of 5-10 years were selected for the study. The PEFR was measured by making the participant seated comfortably. One peak flow meter was used for 25 children and mouthpiece was changed for each student. Results: The PEFR value among and male and female participants was analyzed statistically (Table 2). The mean value of male and female study population was 169.53±37.38 and 146.24±33.01 respectively. The difference in the mean values were statistically significant (p=0.001) and found to be high in male participants. The Pearson correlation r between PEFR with height is 0.463, thus showing a positive correlation with the p˂0.001 which is statistically significant. The Pearson correlation r between PEFR and chest circumference is 0.335 thus indicating a positive correlation between PEFR and chest circumference. Conclusions: From the present study, the normal values of PEFR has been deduced for the healthy school children in our geographical area. Further, it was found that the height and chest circumference are influencing factors for PEFR. Further regression equation has been derived that can help us to find the approximate PEFR values with the help of height and chest circumference of the children.